Phenolic constituents of Trifolium resupinatum var. minus: Protection against rosiglitazone induced osteoporosis in type 2 diabetic male rats - Mona E. S. Kassem, Mona M. Marzouk, Amani A. Mostafa, Wagdy K. B. Khalil, Hoda F. Booles (Journal of Applied Pharmaceutical Science, 2017)
Thiazolidinediones, an antidiabetic drug, promote bone loss and provoke fractures, suggesting a protective role of phytoestrogens rich herbal supplement along with rosiglitazone. The aqueous methanol extract (AME) of Trifolium resupinatum L. var. minus Boiss. (Fabaceae) and defatted AME (DAME) protective effects were assessed against rosiglitazone (Ros) inducing osteoporosis in type 2 diabetic male rats. Eighty male Albino rats (10/group) were used. OPG, RANKL and β2- microglobulin serum levels, femur BMD (Dexa) and OC, COL and ACP5 osteogenic genes mRNA (qRT-PCR) were evaluated in Ros-rats + AME or DAME (24, 12, 6 mg/kg bw/d, each). Ros-rats + DAME (24 mg/kgbw) revealed the most significant effects on bone biomarkers. It modulated OPG (ng mL-1), RANKL (pg mL-1) and β2- microglobulin (μg mL-1) serum levels. It also improved BMD (mg cm-2) of proximal, distal and total femur bones compared to Ros-rats and up-regulated OC and COL and down-regulated ACP5 expressions. The phenolics of bioactive extract (DAME) were evaluated. Twelve known phenolics were isolated and characterized by chromatographic, chemical and spectral techniques. Their HPLC profiling was also analyzed and showed major phenolics; chlorogenic acid > formononetin> quercetin> pseudobaptigenin. DAME in combination therapy with rosiglitazone provides protective effect on bone, possibly due to its phenolics.
Keywords: Persian clover, Thiazolidinediones, diabetes, serum bone markers, bone mineral density, osteogenic genes, phytoestrogens.